Proyectos de inversión pública y el acceso al servicio integrado de agua, desagüe y electrificación en la región Loreto 2012-2021 - Asin Vasquez, Jhon Pool (2023)
The objective of this research work is determine if the public investment projects executed by the Central Government in Loreto, the Regional Government of Loreto and the Local Governments of Loreto present general significance on the access to the integrated service of water, drainage and electrification in the Loreto region. The research was of a quantitative type, causal level and non-experimental design with longitudinal data. After applying the OLS regression for time series and pass the significance test at 90% confidence, It was determined that the model that considers as independent variables the amounts in public investment projects in charge of the Central Government, Regional Government and Local Governments in Loreto with a lag period during 2012-2021, does not explain the percentage of households with access to the integrated service. To complement the research, the year 2021 was excluded from the model due to the effects of covid-19 on household compliance in paying of basic services, concluding that at least one of the explanatory variables are significant and together they determine 80.75% of the variations in the percentage of households with access to the integrated service; and, that by increasing the amount accrued in public investment projects under the Central Government by 1%, the percentage of households with access to the integrated service will increase by 0.066%.